Dietary patterns and lifestyle characteristics in adults: results from the Hellenic National Nutrition and Health Survey (HNNHS). (June 2019) - ,; ,; Fappa, E.; Theodoraki, E.-M.; Trichia, E.; Sialvera, T.-E.; Varytimiadi, A.; Spyreli, E.; Koutelidakis, A.; Karlis, G.; Zacharia, S.; Papageorgiou, A.; et al.
Abstract: Objectives: The objective of this study was to identify and describe different dietary patterns in a nationally representative sample of Greek adults and to assess potential associations with lifestyle characteristics. Study design: This was a cross-sectional study. Methods: Dietary patterns were derived by principal component analysis using individual dietary data (24-h recall) of 3552 participants of the Hellenic National Nutrition and Health Survey (HNNHS). Analysis of variance and chi-squared test were used to determine the lifestyle characteristics of the participants following each pattern. Results: Three dietary patterns were identified explaining 16.5% of variance; a traditional pattern, loading positively on olive oil, non-starchy vegetables, and cheese; a Western pattern, loading positively on refined grains, processed meats, and animal fats; and a prudent pattern, loading positively on fruits, whole grains, and yoghurt and negatively on fast food. A fourth, snack-type pattern, loading positively on sweets, salty snacks, and nuts, was identified in women. Primary crude results revealed an association between dietary patterns and socio-economic status. In multivariate analysis, highest adherence to the prudent pattern was associated with higher protein and unsaturated fat intake and lower energy and saturated fat intake (all P  ≤ 0.05); the Western and traditional patterns were associated with higher energy and total and saturated fat intake. The traditional pattern was additionally associated with higher monounsaturated fatty acids intake, whereas the Western pattern, with higher alcohol intake (all P  ≤ 0.001). Conclusions: These findings are valuable for understanding the dietary behaviors of adults in Greece and enabling more focused public health policies for the promotion of healthier food behaviors in the future. Highlights: Three major dietary patterns among Greek adults: traditional, Western, and prudent. The Mediterranean diet is progressively disappearing in the Mediterranean countries. High heterogeneity in diet patterns further associated with socio-economic factors. Snack-type pattern only in women (young, single, high education, employed, and smokers). Low sleep quality and high depression prevalence associated with unhealthy patterns.